Dispersal and water age of the plumes from the four outlets of the Pearl River during the dry winter - Guang Zhang; Pengpeng Hu; Suan Hu; Yuren Chen; Junpeng Zhao; Chunlei Ma; Heng Zhang; Wenping Gong (Marine Pollution Bulletin, 2026)

Subsurface soil as a hotspot for iron-bound organic carbon loss driven by moisture and microorganisms during seasonal freeze-thaw period - Yuxin Tian; Maidinuer Abulaizi; Zailei Yang; Tianle Kou; Yuanbin Jia; YunPeng Hu; Mo Chen; Hongtao Jia (Applied Soil Ecology, 2026)

Cover Image - Yuanliang Duan; Wenqiong Wu; Zhipeng Huang; Lu Zhang; Chengyan Mou; Zhongmeng Zhao; Han Zhao; Jun Du; Jian Zhou; Qiang Li (Reviews in Aquaculture, 2025)
The cover image is based on the article Research on Longsnout Catfish ( Leiocassis longirostris ) Worldwide: Current Status and Future Prospects by Qiang Li et al., https://doi.org/10.1111/raq.70092 . image

Research on Longsnout Catfish ( Leiocassis longirostris ) Worldwide: Current Status and Future Prospects - Yuanliang Duan; Wenqiong Wu; Zhipeng Huang; Lu Zhang; Chengyan Mou; Zhongmeng Zhao; Han Zhao; Jun Du; Jian Zhou; Qiang Li (Reviews in Aquaculture, 2025)
The longsnout catfish ( Leiocassis longirostris ) is primarily found in the Yangtze River Basin in China. This species has been studied for more than 40 years, predominantly by researchers at the Fisheries Research Institute, Sichuan Academy of Agricultural Sciences (Sichuan Fisheries Research Institute), Southwest University, and the Institute of Hydrobiology of the Chinese Academy of Sciences. Concurrently, multiple research institutions worldwide have also conducted studies on this species, including Aberystwyth University and the University of Copenhagen in Europe, the University of Hawaii and the University of Prince Edward Island in North America, Korea Maritime and Ocean University and the ICAR National Bureau of Fish Genetic Resources in Asia, and the University of Adelaide in Oceania. Most studies on L. longirostris have focused on aquaculture techniques. In this review, we consider all studies on L. longirostris from 1974 to 2023, providing a detailed analysis of the current research status regarding its aquaculture, physiological characteristics, germplasm resources, new variety development, and deep processing. We also speculated on potential future research directions. In summary, this review establishes a solid foundation for future scientific research and aquaculture production of the species, which may promote the further development of new varieties and value‐added products derived from L. longirostris .

Root exudates of Salix cupularis orchestrate the accumulation of soil carbon and nitrogen in the rhizosphere during the restoration of a desertified alpine meadow - Qi Li; Fei Yan; Dongming Chen; Jiqiong Zhou; Zhouwen Ma; Yanfu Bai; Xingpeng Hu; Congyu Ma; Abeer S. Aloufi; Feida Sun; Anna Gunina; Jian Zhang; et al. (Applied Soil Ecology, 2025)

Short-term tillage regime exerts stronger effects than straw return on carbon and nitrogen transformation in rice rhizosphere - Xinhu Guo; Peixin Guo; Shupeng Huang; Zongyi Tong; Qian Zhang; Haishui Yang (Applied Soil Ecology, 2025)

Fully coupled morphological modelling under the combined action of waves and currents - Wei Li; Yiming Zhang; Peng Hu (Advances in Water Resources, 2025)

Effects of bed sediment conditions on debris flow propagation from the two-phase flow modelling perspective - Binghan Lyu; Yue Li; Peng Hu (Advances in Water Resources, 2024)